TANAH ASET PT. PANCA WIRA USAHA MILIK PERUSAHAAN DAERAH PROPINSI JAWA TIMUR DIDUDUKI MASYARAKAT - karyoto karyoto (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2018)
The origin of land asset PT Panca Wira Usaha owned by East Java Province company, obtained from former land of western rights, relics of Dutch company at the time of colonize in Indonesia. Dutch dominate the land through Verenigde Oost - Indische Compagnie (VOC). VOC is a Dutch-owned legal entity engaged in trade. Before VOC control land in Indonesia, the control of the land is still done by Kings in the territory of his power, as well as by the customary law community within its territory. When the VOC came to Indonesia around 1577 with the intention to trade and made the kingdom of Mataram a protectorate and since then the role of local officials gradually began to change. The arrival of VOC in Indonesia aims for the following matters: Prevent competition among Dutch traders Obtain a trade monopoly in south Asia or exclusively master the spices both in producing and trading VOC as a Dutch-owned legal entity engaged in trade, it is a little more know the public legal aspects as the influence of Roman law, although no relation belongs to the land, but VOC make agreements with the landowners as if to voc charge as an obligation to rent land through an agreement that is essentially so that the visible aspect of democracy appears. The Dutch Government established factories in big cities after the VOC successfully mastered inland village for agriculture, plantation and others. One of the factory is Oil Factory